Management of white rust (Albugo cadida)of mustard (Brassicajulacea)b y altering sowing date and fungicides* - BISWAS, CHINMAY; SINGH, RAVINDRA; TEWARI, R B (The Indian Journal of Agricultural Sciences, 2011)
Mustard (Brassica juncea (L.) Czern. & Coss.) is the principal rabi oilseed crop in India which covers 22% of area and contributes 25% of production of total oil seed crops. The average productivity of the crop in India is nearly I. tonneiha. The crop is affected by a number of diseases of which white rust [Albugo candida (Pers. ex. Lev.) Kuntze] is the serious one and has the potential to cause up to 89.9 % yield loss due to foliar and floral infection (Godika et al. 2001)...........